Advancing Teacher Competencies through Lesson Study for Learning Community (LSLC): Insights from SMP Muhammadiyah 8 Batu City (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
Lesson Study for Learning Community (LSLC) is a collaborative approach designed to enhance the quality of teaching and learning by addressing the professional development needs of both teachers and students. This study analyzes the cognitive understanding and practical abilities of teachers at SMP Muhammadiyah 8 Batu City (SMPM 8) in implementing LSLC. The objectives include evaluating teachers’ knowledge and competencies related to LSLC, assessing progress in planning, conducting, and reflecting on LSLC-based activities through pre-test and post-test assessments, and providing foundational insights into the effectiveness of LSLC implementation for future improvement. This descriptive study, conducted from August 2023 to April 2024, involved 10 teachers actively engaged in LSLC activities. Data were collected using questionnaires, observations, written tests, and document analysis and analyzed descriptively. The results indicate significant improvements in teachers' cognitive understanding and practical implementation of LSLC, with average scores increasing from 58 (pre-test) to 88 (post-test). These findings underscore the effectiveness of LSLC workshops in enhancing teacher competencies, particularly in collaborative planning, student engagement, and reflective practices. The study offers initial insights into teachers’ knowledge of LSLC, which can inform the development of targeted professional development programs. It also highlights effective strategies for scaling LSLC practices to other schools and contributes to the broader understanding of LSLC's impact on teacher development and learning quality, providing evidence to inform educational policy at local and district levels.